Pengaruh Zikir Terhadap Ketenangan Dan Kebahagiaan Manusia, Perspektif Qurani - Mohammad Bisri (Universitas Cokroaminoto Yogyakarta, 2017)
Humility and human happiness are a very important aspect. Many factors affect human serenity and happiness, such as prayer, zakat and charity, fasting, pilgrimage and dhikr. but only one that is easy for everyone throughout the world in various circumstances and environment and has a very decisive influence on human happiness that is dhikr to Allah. On the contrary, human beings no longer use it to recite to Allah, then suddenly his happiness is pulled out from his bosom; it's just gone missing its memory. There was a sad feeling, his chest suddenly felt tight and narrow, not even infrequently his life became meaningless.